Approximately half of patients with coronary spastic angina had pathologic exercise tests. Issue 1 (July 2016) - Sueda, Shozo; Miyoshi, Toru; Sasaki, Yasuhiro; Sakaue, Tomoki; Habara, Hirokazu; Kohno, Hiroaki
Abstract: Objectives: We examined the clinical usefulness of treadmill exercise tests (TETs) in diagnosing coronary spastic angina (CSA). Methods: We performed the TETs and 24-h Holter monitoring in 300 CSA patients consisting of 152 patients with rest angina, 77 patients with effort angina, and 71 patients with rest and effort angina. Organic stenosis (>75%) was observed in 44 patients. Multiple spasms were recognized in 204 patients (68%). Results: Positive TETs were recognized in 113 patients (38%) and borderline was observed in 30 patients (10%). Positive response was significantly higher in patients with organic stenosis than those without fixed stenosis (63.6% vs. 33.2%, p  < 0.001). Moreover, ST elevation was more frequent in patients with organic stenosis than those without fixed stenosis (27.3% vs. 1.2%, p  < 0.001). Positive response in patients with effort angina (46.8%) was higher than those in patients with rest angina (33.6%) and rest and effort angina (36.6%), but not significant. Positive response was not different between single spasm and multiple spasms. In all 300 patients, ST segment elevation was observed in only four patients (1.3%) on the 24-h Holter monitoring. Conclusions: TET was useful in documenting ischemia in patients with CSA. More than a third of patients with CSA had positive TETs. Moreover, we obtained the pathologic TET response in approximately half of patients with CSA.